Respuesta :

For this case we convert the mixed numbers into fractions:

[tex]7 \frac {5} {6} = \frac {6 * 7 + 5} {6} = \frac {42 + 5} {6} = \frac {47} {6}\\3 \frac {1} {12} = \frac {12 * 3 + 1} {12} = \frac {36 + 1} {12} = \frac {37} {12}[/tex]

Rewriting the expression:

[tex]\frac {47} {6} - \frac {37} {12} =\\\frac {12 * 47-6 * 37} {6 * 12} =\\\frac {564-222} {72} =\\\frac {342} {72} =[/tex]

We simplify:

[tex]\frac {171} {36} =\\\frac {57} {12} =\\\frac {19} {4}[/tex]

Thus, the simplified form is:[tex]\frac {19} {4}[/tex]

Answer:

[tex]\frac {19} {4}[/tex]

ACCESS MORE